Database Development on Surveilance System of Tuberculosis Cases Management through Public Private Mix (PPM) Approach in Health Office of Surabaya - Yuliandari, Rosita Dwi; Syahrul, Fariani; Suryaningdiah, Daniek (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Surabaya as urban area with high level urbanization and population density has become one of the biggest contributor of Tuberculosis (TB) cases in East Java Province. The number of new cases which are confirmed bacteriologically Tuberculosis lung in 2017 for 2.842 cases and the total number of Tuberculosis cases found and treated for 6.488 cases. This research used descriptive design. The design of this database model development was begun from creating output components, processing components, and identifying input components. The data collecting was done by indepth Interview to the Head of Infectious Disease Prevention and Control Section and two TB Wasor in Surabaya City Health Office of which output components consisted of percentage of health service facility that had implemented the TB service based on the standards, performing mandatory notification, accredited and certified, the number of professional organizations involved, and the number of community organizations involved. Process components consisted of data analysis of TB Public Private Mix, data interpretation and result dissemination. The input component was to analyze the material needed on database development of TB case management surveillance system through Public Private Mix approach formed recording and reporting, hardware-software requirements, human resources availability in surveillance system and methods/ procedures used in system development. Need to be undertaken a test from the development of a database that has been designed and conduct monitoring and evaluation therefore it can be input for further improvement. Keywords: Tuberculosis, Surveillance, System